2013
DOI: 10.1620/tjem.231.243
|View full text |Cite
|
Sign up to set email alerts
|

The <i>FOXL2</i> Mutation (c.402C>G) in Adult-Type Ovarian Granulosa Cell Tumors of Three Japanese Patients: Clinical Report and Review of the Literature

Abstract: Adult-type granulosa cell tumor (AGCT) is a rare class of malignant ovarian tumor with unique features, characterized by slow growth, late recurrence, relatively good prognosis and unified cause in almost all patients. The forkhead box L2 (FOXL2) gene encodes an essential transcription factor in the ovary. FOXL2 is important in female sex determination, follicle recruitment, and granulosa cell development. About 70-97% of AGCTs were reported to carry a somatic mutation c.402C>G (C134W) in the FOXL2 gene. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…DNA was extracted from both yellowish and necrotic portions in the formalin‐fixed paraffin‐embedded specimen. The design of primer sequences and PCR reactions was carried out as previously reported . The products were analyzed by Sanger sequencing.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted from both yellowish and necrotic portions in the formalin‐fixed paraffin‐embedded specimen. The design of primer sequences and PCR reactions was carried out as previously reported . The products were analyzed by Sanger sequencing.…”
Section: Case Reportmentioning
confidence: 99%
“…The design of primer sequences and PCR reactions was carried out as previously reported. 7 The products were analyzed by Sanger sequencing. The FOXL2 point mutation (402C!G) could not be detected in either the yellowish or necrotic portion (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…Among all these genes, Foxl2 has attracted particular attention during the last 15 years as a key player due to its involvement in sex differentiation and oogenesis [Baron et al, 2005;Benayoun et al, 2009;Veitia, 2010;Boulanger et al, 2014;Georges et al, 2014a;Nicol and Yao, 2014]. A substantial amount of information on FOXL2 action was initially acquired from studies in humans and other mammals, and many excellent reviews have already been published, most centered on the roles of FOXL2 in normal or pathological female development in mammals and/or vertebrates [Fuhrer, 2002;Baron et al, 2005;De Baere et al, 2005;Benayoun et al, 2009Benayoun et al, , 2010Beysen et al, 2009;Kobel et al, 2009;Pisarska et al, 2011;Uhlenhaut and Treier, 2011;Biason-Lauber, 2012;Caburet et al, 2012;Verdin and De Baere, 2012;Takahashi et al, 2013;Georges et al, 2014a;Rosario et al, 2014;Leung et al, 2016]. The present review focuses on ' foxl2 ' genes in light of recent findings on their evolution, expression, and roles in sex differentiation in animals.…”
mentioning
confidence: 99%
“…50 Several studies have reported that approximately 70-97% of adult granulosa cell tumors carry a somatic c.402C>G missense point mutation in the FOXL2 gene. [51][52][53] The FOXL2 gene encodes a transcription factor that is expressed in different tissue types, including the ovaries and pituitary gland. This gene plays an essential role in ovarian development and differentiation.…”
Section: Pure Sex Cord Tumorsmentioning
confidence: 99%